Parental Autonomy Granting, Peer Attachment and Problematic Internet Use Among Chinese Adolescents: The Moderating Effect of School Climate. - Wu, Yu-Qi; Chen, Pei; Li, Sheng-Nan; Huang, Xin-Yi; Nie, Yan-Gang (Child Psychiatry & Human Development, 2026)
While the correlation between parental autonomy granting and adolescents' problematic Internet use (PIU) has been confirmed, the processes underlying this connection have not been thoroughly investigated. Drawing on the ecological systems theory, this study sought to investigate the mediating mechanism of peer attachment and the moderating mechanism of school climate that link parental autonomy granting to PIU. A two-wave longitudinal design was employed with a time interval of six months. The participants were 852 adolescents who attended three middle schools located in Guangdong Province, China. Self-report questionnaires were used to obtain data on demographics, parental autonomy granting, peer attachment, school climate, and PIU. The findings indicated that peer attachment significantly mediated the link between parental autonomy granting and adolescent PIU. A positive school climate significantly moderated the influence of parental autonomy granting on peer attachment and the influence of peer attachment on PIU. Specifically, the association between parental autonomy granting and peer attachment and the association between peer attachment and PIU were more pronounced when the school climate was perceived to be positive. This research underscores the possible significance of peer attachment in the association between parental autonomy granting and PIU and offers valuable insights for mitigating the negative outcomes of PIU.